2016
DOI: 10.1089/met.2015.0094
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cognitive Performance Among Chinese ≥50 Years: A Cross-Sectional Study with 3988 Participants

Abstract: In our study, MetS is not associated with cognitive performance in elderly Chinese population. However, elderly Chinese with diabetes would have lower cognition function, and the dyslipidemia might be reversely associated with the cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…[24] Age and abdominal obesity were signi cant risk factors for cognitive decline. [16] Studies have failed to show any association between Mets and cognitive impairment; [14,25] however, most studies have shown that participants with metabolic syndrome are associated with increased odds of cognitive impairment, [12,20,24,26,27] which is consistent with our results. Although most studies have shown that Mets and its components play roles in cognitive decline, other studies have suggested that late-life Mets has a protective effect on cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…[24] Age and abdominal obesity were signi cant risk factors for cognitive decline. [16] Studies have failed to show any association between Mets and cognitive impairment; [14,25] however, most studies have shown that participants with metabolic syndrome are associated with increased odds of cognitive impairment, [12,20,24,26,27] which is consistent with our results. Although most studies have shown that Mets and its components play roles in cognitive decline, other studies have suggested that late-life Mets has a protective effect on cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…For example, it was estimated that 11 million deaths world-wide can be attributed to MetS annually [3]. Although MetS has traditionally primarily been linked to CVD, studies suggest that MetS [47] and metabolic abnormalities more generally [79] may also be related to cognitive impairment as a type of organ dysfunction that burdens the global economy to extents similar to CVD [10]. Chronically elevated blood glucose levels, for instance, have consistently been associated with an increased risk of future cognitive impairment [11].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse relationship between Digit symbol test scores and increasing numbers of MetS constituents has also been reported ( Tsai et al., 2016 ). However, other studies did not observe an association between presence of MetS and cognitive performance in the older population ( Chen et al., 2016 ).…”
Section: Discussionmentioning
confidence: 79%